ANALISIS AERODINAMIKA DAN AEROAKUSTIK AIRFOIL WORTMANN FX63-137 - Muhammad Zidane Athaya Zulkipli; I Kade Wiratama; I Gusti Ngurah Ketut Yudhyadi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
The aerodynamics and aeroacoustics of airfoils are important considerations in the design of wind turbine blades. Improving wind turbine efficiency by maximizing power requires consideration of minimizing noise levels for environmental health. There aren't many studies that use the Wortmann FX63-137 airfoil for both noise prediction with Large Eddy Simulation (LES) and aerodynamic analysis using the SST k−ω model. This study seeks to examine how variations in the angle of attack impact the aerodynamic performance and noise levels of the airfoil. The ANSYS Fluent with the SST k−ω model was used to simulate the airfoil's aerodynamic performance, and LES was used to analyze the airfoil's aeroacoustic performance as the angle of attack changed from 0° to 12°. The results show that increasing the angle of attack raises the CL to a maximum at 12° but also increases CD, which reduces aerodynamic efficiency. Noise levels increase as the angle of attack increases, with peak noise occurring at the trailing edge. This study provides insights for optimizing the design of more efficient wind turbine airfoils while considering environmental noise levels..